EXPLORING THE EXPERIENCES OF PRISONERS ABOUT MANAGING THEIR STUDIES IN A DISTANCE LEARNING ENVIRONMENT: A CASE OF NAMIBIA - Mahlangu Vimbi Petrus (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This qualitative study delves into the experiences of incarcerated individuals in Namibia as they navigate the challenges and opportunities of studying in a distance learning environment. The research aims to uncover the unique perspectives, obstacles, and strategies employed by prisoners in managing their educational pursuits while incarcerated, with the goal of informing policy and practice in correctional education. Utilizing in-depth interviews as the primary method of data collection, the study adopts an interpretive paradigm to delve deeply into the subjective experiences and meanings attributed by participants to their educational endeavors within the prison context. Following the transcription of the interviews, the author engages in thematic analysis to identify recurring patterns and themes, facilitating a comprehensive understanding of the complexities inherent in studying while incarcerated. Through this analytical lens, the study sheds light on the diverse challenges and opportunities encountered by individuals in prison settings, enriching scholarly discourse and informing efforts to enhance access to education and promote rehabilitation within correctional facilities.